ANALISIS FAKTOR DALAM MENGGUNAKAN LAYANAN E-BILL DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Sari, Ema Novita; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to examine some factors which will influence the revenue and the use of e-bill or electronic billing by using Technology Acceptance Model (TAM) approach. The constructions which have been applied in this research i.e. Perceived ease of use, perceived of usefulness, attitude toward usage, behavioral intention to use, and actual use. In this research, the Perceived ease of use will be correlated to perceived of usefulness. Perceived ease of use and perceived of usefulness will be correlated to attitude toward usage. Furthermore attitude toward usage will be correlated to behavioral intention. Moreover, behavioral intention to use will be correlated to actual use. The object of the research is all corporate HALO card prepaid customers at PT. Telkomsel Surabaya who have been applied e-bill. The sample collection in this research has been done by using purposive sampling. The data is the primary data which has been done by issuing questionnaires. The primary data has resulted 254 questionnaires which can be processed by using SEM (Structural Equation Model) analysis technique and Partial Least Square (PLS) methods.The result of the research shows that Perceived ease of use has positive influence to the perceived of usefulness. Perceived ease of use and perceived of usefulness has positive influence to the attitude toward usage. Attitude toward usage does not have any influence to the behavioral intention to use. Meanwhile, behavioral intention to use does not have influence to the actual use in using e-bill.Keywords: e-bill, Technology Acceptance Model, Perceived ease of use, perceived of usefulness, attitude, behavioral intention to use, actual use